Natural characteristics analysis of aircraft wing box based on finite element method and measured data - Wei, Zhang; Ling, An Lu; Geng, Xu Yi; Ping, Wu Xiu; Qiang, Gao Guo (JVE Journals, 2018)
Compared with other mechanical products, aircraft structures have more rigorous requirements on flying performance, safety, reliability and service life. Based on the finite element method (FEM), the key component of the wing box model is explored in this paper, which provides a reference for the structure design and manufacture of aircraft wing box. The three-dimensional point cloud data of components are obtained by optical measurement systems, the deviation analysis between the point cloud model and the nominal model is carried out as a prerequisite, and then the natural characteristics of the model is analyzed. The results show that 99.15 % of the measured points have deviations within 0.38 mm, which verifies the accuracy of the nominal model. The first six modes are all bending modal shape, and the larger amplitude region mainly occurs in the wing ribs, which means its bending strength should be improved for structure design. Besides, the sixth-mode simultaneously result in front spar, stringer and rib bending vibration.
Keywords: wing box; point clouds processing; natural characteristics; finite element method